Meeting of the ASEAN Heads of Government and the Prime Minister of Japan, Manila, 14-15 December 1987 - Meeting of the Asean Heads of Goverment (1987 : Manila, Philippines) (Jakarta : ASEAN Secretariat, 1987)
32